Mucus-penetrating budesonide nanosuspension enema for local treatment of inflammatory bowel disease. (December 2018) - Date, Abhijit A.; Halpert, Gilad; Babu, Taarika; Ortiz, Jairo; Kanvinde, Pranjali; Dimitrion, Peter; Narayan, Janani; Zierden, Hannah; Betageri, Kalpana; Musmanno, Olivia; Wiegand, Helen; Huang, Xinglu; et al.
Abstract: Inflammatory bowel disease (IBD) is a chronic inflammatory gastrointestinal disorder that affects more than 1 million individuals in the USA. Local therapy with enema formulations, such as micronized budesonide (Entocort ® ), is a common strategy for treating patients with distally active IBD. However, we hypothesize that micronized particulates are too large to effectively penetrate colorectal mucus, limiting the extent of drug delivery to affected tissues prior to clearance. Here, we describe the development of a budesonide nanosuspension (NS) with the appropriate surface coating and size to enhance penetration of colorectal mucus and ulcerated colorectal tissues. We demonstrate that model fluorescent polystyrene (PS) particles ∼200 nm in size with a muco-inert Pluronic F127 coating provide enhanced mucosal distribution and tissue penetration in mice with trinitrobenzenesulfonic acid (TNBS)-induced IBD compared to model 2 μm PS particles coated with polyvinylpyrollidone (PVP), the stabilizer used in the clinical micronized budesonide formulation. We then used a wet-milling process to develop a budesonide NS formulation with a muco-inert Pluronic F127 coating (particle size ∼230 nm), as well as a budesonide microsuspension (MS) stabilized with PVP (particle size ∼2 μm). Using an acute TNBS mouse model of IBD, we show that daily budesonide NS enema treatment resulted in a significant reduction in the macroscopic (decreased colon weight) and microscopic (histology score) symptoms of IBD compared to untreated controls or mice treated daily with the budesonide MS enema. Further, we show that the budesonide NS enema treated mice had a significantly reduced number of inflammatory macrophages and IL-β producing CD11b + cells in colon tissue compared to untreated controls or mice treated with the budesonide MS enema. We conclude that the nano-size and muco-inert coating allowed for enhanced local delivery of budesonide, and thus, a more significant impact on local colorectal tissue inflammation.